Realization of Children's Language Politeness at RT 009 Kelurahan Rawamangun - Wayan Pageyasa (Journal of Indonesian Language Education and Literary, 2017)
Politeness is very important for everyone, wherever he is. The application of politeness (including language politeness) reflects the culture of a society. Given the importance of this language politeness, it should be familiarized with children from an early age. The problem of this research is how is the realization of children's language politeness at RT 09, Kelurahan Rawamangun? The purpose of this research is to reveal and explain the facts of language usage in relation to the realization of language politeness by the children at RT 09, Kelurahan Rawamangun. The theory used as the foundation in this research is Leech and Brown-Levinson's politeness theory. This study used a qualitative approach with pragmatic content analysis design. The research site is at RT 009, Kelurahan Rawamangun. The data source of this research is the children at RT 009, Kelurahan Rawamangun which is under seven years old. While the data of this research is conversations conducted by the children while playing at neighborhood. The results of this study reveals that children under seven years old still use positive politeness strategy to express their desires. In this study, it is found also violations of politeness by children. Children who are accustomed to rough language (impolite) are children of uneducated families.